Insilico Identification Of Potential Inhibitors For Farnesyl Transferase From Aloe Vera For Cancer - P.T.V LAKSHMI,; PA RAJALAKSHMI, (International Journal of Pharma and Bio Sciences, 2011)
Cancer is one of the major life threatening diseases worldwide. Many studies are in progress to inhibit the rate of distribution of the proteins involved in cancer. The Aloe Vera compounds were checked against the molecular targets of cancer by molecular docking studies. The compounds n-Hexadecanoic acid and tertadecanoic acid were found to interact more towards the target protein showing highest Dock score and more number of Hydrogen bonds. The study was further enlarged with cross reference confirmation with reference ligand (co-crystallized ligand) which has been bounded with selected molecular target protein. We concluded that Aloe Vera, with interesting biological properties and structural diversity, have often served as valuable lead drug candidate for the treatment of many diseases replacing the chemically synthesized drugs which causes side effects.